Investigation of the influence of platinum content on the characteristics of membrane-electrode assemblies of a polymer electrolyte fuel cell - Opakhai С.; Kuterbekov К.А.; К.Ж.; Kabyshev А.М.; Kubenova М.М.; Aidarbekov Н.К.; Zeinulla Ж.С.; Pangaliev Е.М. (Recent Contributions to Physics, 2025)
This work presents an analysis of the impact of key parameters, such as platinum content, temperature, and oxygen concentration, on the performance of membrane-electrode assemblies (MEAs) used in fuel cells. The primary objective of the study is to develop recommendations for optimizing catalyst compositions to achieve a balance between performance and cost-effectiveness. Modeling was conducted for three types of catalysts: pure platinum (Pt), platinum with nickel (Pt-Ni), and platinum with cobalt (Pt-Co). The dependencies of voltage, power, and efficiency on current density were investigated, taking into account activation, ohmic, and mass transport losses. To assess the stability of the catalysts, the parameter of voltage variation (ΔV) was used within the range of operating loads. The results of the study demonstrate that platinum content has the most significant impact on the performance of MEAs. The optimal platinum content is 1.0 relative units, at which the maximum values of power and efficiency are achieved. However, alloyed catalysts (Pt-Ni and Pt-Co) exhibit stability at lower costs, making them promising for application. Additionally, the characteristics were found to depend on temperature and oxygen concentration, emphasizing the importance of controlling operating conditions.